2013
DOI: 10.1007/s10059-013-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adenoviral Transfection of the Keratinocyte Growth Factor Gene on Epidermal Stem Cells: an In Vitro Study

Abstract: Epidermal stem cells (ESCs) are characterized as slowcycling, multi-potent, and self-renewing cells that not only maintain somatic homeostasis but also participate in tissue regeneration and repair. To examine the feasibility of adenoviral vector-mediated keratinocyte growth factor (KGF) gene transfer into in vitro-expanded ESCs, ESCs were isolated from samples of human skin, cultured in vitro, and then transfected with recombinant adenovirus (Ad) carrying the human KGF gene (AdKGF) or green fluorescent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Monoculture models of the epithelium offer a useful platform to study the re-epithelialization process. The cultures consist of keratinocytes (preferably HaCaT cells, an immortalized human skin cell line [147]), primary keratinocytes, or epidermal stem cells [139,[148][149][150][151]. The cell line is grown in a monolayer in vitro and is subjected to a number of assays relevant to the wound healing process [139].…”
Section: In Vitro Wound Healing Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoculture models of the epithelium offer a useful platform to study the re-epithelialization process. The cultures consist of keratinocytes (preferably HaCaT cells, an immortalized human skin cell line [147]), primary keratinocytes, or epidermal stem cells [139,[148][149][150][151]. The cell line is grown in a monolayer in vitro and is subjected to a number of assays relevant to the wound healing process [139].…”
Section: In Vitro Wound Healing Modelsmentioning
confidence: 99%
“…The cell line is grown in a monolayer in vitro and is subjected to a number of assays relevant to the wound healing process [139]. Many studies have used the presence of cytokines [138,[152][153][154][155], growth factors [148,[156][157][158][159][160], or the expression of several markers of the ECM [161,162] as standards for the measurement of the wound healing processes [139]. Co-culture cell models more closely resemble the in vivo epithelial structure and consist of cells that are normally in communication during the wound healing process.…”
Section: In Vitro Wound Healing Modelsmentioning
confidence: 99%
“…Western blot analysis for KGF expression was carried out using the tissue proteins. Briefly, tissue proteins were obtained from the extracts of the epidermis of mice, and Western blot was performed as described in Li et al 13 Antibody reaction was done with antibodies against KGF (Boster, Wuhan, China; dilution 1: 200), GAPDH (Santa Cruz Biotechnology, Santa Cruz, CA; dilution 1: 2,000).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…11 Keratinocyte growth factor (KGF), known as fibroblast growth factor 7, is a paracrine growth factor for keratinocytes, which could inhibit terminal differentiation of cultured keratinocytes, 12 and stimulate ESCs to growth and cell division. 13 Guo et al. 14 has shown that KGF was required for hair development.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling pathways such as Wnt [ 10 ], TGF-β [ 11 , 12 ], MAPK [ 13 ], Shh [ 14 ], and Notch [ 15 ] are extensively involved in different components of hair follicle morphogenesis and its periodic variation. In addition, some cytokines also play an important role in hair follicle development and hair growth processes, including KGF [ 16 ], IGF [ 17 ], VEGF [ 18 ], EGF [ 19 ], and thymosin β4 [ 20 ], which promote the growth of hair follicles, and FGF-5 [ 21 , 22 ], which inhibits hair growth. MicroRNAs (miRNAs) are endogenously expressed, highly conserved small RNAs with 21–25 nucleotides that are derived from one arm of their precursor with a stem-loop structure that is expressed in specific cells and tissues [ 23 ].…”
Section: Introductionmentioning
confidence: 99%